1989
DOI: 10.1007/bf00286702
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of mitochondrial aldehyde dehydrogenase: genotyping in Chinese, Japanese and South Korean families reveals dominance of the mutant allele

Abstract: Genotyping of mitochondrial aldehyde dehydrogenase (ALDH I) was performed in enzymatically amplified DNA of 20 Chinese, Japanese and South Korean families (85 individuals) and in 113 unrelated persons by employing allele-specific oligonucleotide probes and dot blot hybridization. Genotyping individuals with phenotypic deficiency of ALDH I activity always showed the presence of at least one mutant allele. The data are compatible with a model assuming dominant inheritance of the mutant allele, which we have prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 14 publications
2
32
0
Order By: Relevance
“…Subjects with the mutation typically experience facial flushing and a "disulfiram-like" reaction after ingestion of alcohol. 10,16,17 The dominant-negative behavior of the allele is attributed to tetramer formation by the enzyme, and the activity of the enzyme in heterozygotes is estimated to be 6.25% of normal. 10 As expected from the fact that the mutation is dominant, there was no apparent difference between the drug responses in the heterozygotes and the homozygotes in the study, although the number of homozygotes in the study was too small to perform any separate statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjects with the mutation typically experience facial flushing and a "disulfiram-like" reaction after ingestion of alcohol. 10,16,17 The dominant-negative behavior of the allele is attributed to tetramer formation by the enzyme, and the activity of the enzyme in heterozygotes is estimated to be 6.25% of normal. 10 As expected from the fact that the mutation is dominant, there was no apparent difference between the drug responses in the heterozygotes and the homozygotes in the study, although the number of homozygotes in the study was too small to perform any separate statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…10,16,17 The dominant-negative behavior of the allele is attributed to tetramer formation by the enzyme, and the activity of the enzyme in heterozygotes is estimated to be 6.25% of normal. 10 As expected from the fact that the mutation is dominant, there was no apparent difference between the drug responses in the heterozygotes and the homozygotes in the study, although the number of homozygotes in the study was too small to perform any separate statistical analysis. It might be the case that other mechanisms of bioactivation of NTG can be recruited when ALDH2 activity is decreased for whatever reason, and this could be particularly important in the case of homozygotes for the glu504lys mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ALDH2 alleles encoding the active and inactive subunits are termed ALDH2*1 and ALDH2*2, respectively. Previous studies have shown that both homozygotes and heterozygotes for ALDH2*2 are deficient in ALDH2 activity, suggesting the dominance of ALDH2*2 allele over the allele encoding the active subunit of the isozyme (Crabb et al, 1989;Singh et al, 1989;Xiao et al, 1995).…”
mentioning
confidence: 99%
“…A mutant allele, ALDH2*2, has a single point mutation (G fi A) in exon 12 of the active ALDH2*1 gene and is confined to Asians (Yoshida et al 1984). The mutation results in a substitution of glutamic acid 487 to lysine (E487 K), acting in a dominant negative fashion (Crabb et al 1989, Singh et al 1989, Xiao et al 1996. Individuals with the ALDH2*2 allele exhibit the alcohol-flushing syndrome attributable to an elevated blood acetaldehyde level (Goedde et al 1979, Crabb 1990).…”
Section: Introductionmentioning
confidence: 99%